Tax Planning Analysis on Corporate Income Tax Article 25 At PT Unoson Manado - Sharon Ester Hermien KARLOS; Anneke WANGKAR; Sonny PANGERAPAN (PT Keberlanjutan Strategis Indonesia, 2023)
Tax planning is to minimize the tax burden and implement tax compliance, such as calculating, paying, and reporting the tax payable correctly and punctually. PT Unoson Manado received the SP2DK for the fiscal year 2020 with several findings, including the underpayment of Corporate Income Tax. It is caused by the error of calculating the tax burden. This research will determine whether the tax planning could prevent the calculation error in the subsequent fiscal years. The research design used in this research is qualitative with a descriptive approach. The result of this research shows that there are several things on the fiscal income statement of PT Unoson Manado for the year 2020, such as the costs are not fully specified, there is a difference in the calculation between the commercial depreciation and fiscal depreciation, and analyzing on the applicable tax regulations has not been thoroughly done. Therefore, doing the tax planning with its steps and reconciliation can prevent the calculation error in the subsequent fiscal years.